Pengaruh Remunerasi, Work Engagement dan Promosi Jabatan Terhadap Semangat Kerja Karyawan (Studi Pada PT. Alamjaya Wirasentosa) - Hutasoit, Rifka Elfrida; Simanjorang, Feronica (Universitas Serambi Mekkah, 2024)
Human Resources (HR) are a critical asset for a company's success. Therefore, companies need to pay attention to the welfare of their employees so that employees are more enthusiastic in working. This study aims to analyze the effect of remuneration, work engagement and job promotion on employee work morale at PT. Alamjaya Wirasentosa. The research method used is quantitative with an associative approach, and sampling using a purposive sampling method with 76 respondents as the sample. The total population consists of 314 individuals. The results indicate that the variables of remuneration, work engagement, and job promotion have a positive and significant effect on employee work morale, and all independent variables simultaneously influence employee work morale at PT. Alamjaya Wirasentosa.